Contribution to the Development of Psychocardiology in Cuba as a Branch of Health Psychology - Teresa Rodríguez Rodríguez (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Health Psychology, as a branch of psychology, studies the influence of psychic factors on the course and evolution of the health-illness process. A key role of a health psychologist is to help to turn knowledge into healthy behaviors. Since the beginning of the 21st century, new considerations and proposals for psychological interventions related to the treatment of cerebrovascular disease have emerged to improve people's cardiovascular health. This report aims at showing the results of research studies addressing the psychological care of patients with cerebrovascular disease, which have been considered as theoretical, practical and methodological aspects contributing to the development of Psychocardiology in Cuba.